2007
DOI: 10.1111/j.1528-1167.2007.01304.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of Spontaneous Seizures after Experimental Status Epilepticus: Implications for Understanding Epileptogenesis

Abstract: Summary:This report examines several concepts concerning the latent period to the first convulsive seizure, subsequent increases in seizure frequency, and possible mechanisms of epileptogenesis after kainate-induced status epilepticus. Previous data concerning the latent period and seizure progression from intermittent and continuous behavioral monitoring are compared, and hypothetical mechanisms of acquired epilepsy are discussed. Data involving electrographic recordings with tethered animals or with radiotel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 36 publications
3
48
0
1
Order By: Relevance
“…Third, the severity and duration of SE determines the duration of the latency until the first spontaneous seizures. For instance, using continuous video-EEG recordings (with depth electrodes in the dentate gyrus) in the repeated low-dose pilocarpine model that we used in most of our antiepileptogenesis studies, latency to spontaneous seizures is approximately 1 week after SE in most rats (M. Rattka and C. Brandt, unpublished observations) and similar or longer latent periods have been reported by several other studies with continuous monitoring in different post-SE models of TLE (Williams et al, 2007;Sloviter, 2008). In this respect, it is important to note that the 688 LÖSCHER AND BRANDT duration of the latent period depends on the type of induction and severity of the initial SE, ranging from approximately 7 days in the pilocarpine model (Goffin et al, 2007) to Ͼ30 days in models with electrical induction of SE (Nissinen et al, 2000).…”
Section: Problems Associated With Drug Testing In Post-status Epileptsupporting
confidence: 74%
“…Third, the severity and duration of SE determines the duration of the latency until the first spontaneous seizures. For instance, using continuous video-EEG recordings (with depth electrodes in the dentate gyrus) in the repeated low-dose pilocarpine model that we used in most of our antiepileptogenesis studies, latency to spontaneous seizures is approximately 1 week after SE in most rats (M. Rattka and C. Brandt, unpublished observations) and similar or longer latent periods have been reported by several other studies with continuous monitoring in different post-SE models of TLE (Williams et al, 2007;Sloviter, 2008). In this respect, it is important to note that the 688 LÖSCHER AND BRANDT duration of the latent period depends on the type of induction and severity of the initial SE, ranging from approximately 7 days in the pilocarpine model (Goffin et al, 2007) to Ͼ30 days in models with electrical induction of SE (Nissinen et al, 2000).…”
Section: Problems Associated With Drug Testing In Post-status Epileptsupporting
confidence: 74%
“…The key points are: (1) learning destabilizes both the activity and connectivity of a neural system, (2) there is a certain level of connectivity, called critical connectivity, that optimizes brain performance, and (3) there are homeostatic mechanisms that maintain stable levels of activity and critical connectivity in the face of the destabilizing effects of learning.…”
Section: Background: Hebbian Learning Neuronal Avalanches and Criticmentioning
confidence: 99%
“…There is an enormous number of ways in which plasticity can go wrong at all levels of description [2][3][4][5][6][7][8][9]. Particularly at the genetic level, the process of epileptogenesis is a bewildering complex with many contributory factors.…”
Section: Introductionmentioning
confidence: 99%
“…These alterations include increased excitation and decreased inhibition of hippocampal and cortical principal neurons (Cobos et al 2005;FIG. (Xiang et al 2006). Rats injected with kainic acid have been extensively studied as a model of temporal lobe epilepsy (TLE; Williams et al 2007). These animals, after a latent period, exhibit spontaneous, unprovoked seizures and share many elements of hippocampal pathology with human TLE patients, including loss of neurons in the dentate gyrus, mossy fiber sprouting, and hyperexcitability of CA1 pyramidal neurons (Dudek et al 2002;Wenzel et al 2000;Williams et al 2007).…”
Section: Gabaergic Inputs To Interneurons In Epilepsy and Brain Malfomentioning
confidence: 99%
“…Rats injected with kainic acid have been extensively studied as a model of temporal lobe epilepsy (TLE; Williams et al 2007). These animals, after a latent period, exhibit spontaneous, unprovoked seizures and share many elements of hippocampal pathology with human TLE patients, including loss of neurons in the dentate gyrus, mossy fiber sprouting, and hyperexcitability of CA1 pyramidal neurons (Dudek et al 2002;Wenzel et al 2000;Williams et al 2007). Relevant to the studies described here, Morin and colleagues (1999), using electron microscopy, found layer-specific alterations in GABA synapses onto CA1 interneurons in kainic acid-injected rats.…”
Section: Gabaergic Inputs To Interneurons In Epilepsy and Brain Malfomentioning
confidence: 99%